2017
DOI: 10.1017/s0031182017001913
|View full text |Cite
|
Sign up to set email alerts
|

Haemoparasites of the pied flycatcher: inter-population variation in the prevalence and community composition

Abstract: The prevalence and community composition of haemoparasites can substantially differ among avian host populations, which may lead to different selection pressures. Therefore, information about these parameters is crucial for understanding, e.g. the inter-population variation in host life history traits. Here, we molecularly screened a population of a long-distance migrant, the pied flycatcher Ficedula hypoleuca, from central Poland for the presence of three genera of blood parasites: Haemoproteus, Plasmodium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…It is possible that the infection with this lineage was transmitted outside Germany, as pied flycatchers, wintering in Africa, are the only long-distance migratory bird species in our study and infection with the PFC1 lineage might be vectored from dipteran vectors in Africa. However, the distribution of vectors on wintering and breeding grounds, especially for Haemoproteus , is poorly understood (Dubiec et al, 2017) and transmission of PFC1 lineage possibly also occurs in Europe (Jones, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the infection with this lineage was transmitted outside Germany, as pied flycatchers, wintering in Africa, are the only long-distance migratory bird species in our study and infection with the PFC1 lineage might be vectored from dipteran vectors in Africa. However, the distribution of vectors on wintering and breeding grounds, especially for Haemoproteus , is poorly understood (Dubiec et al, 2017) and transmission of PFC1 lineage possibly also occurs in Europe (Jones, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…hPFC1 appears to be a specialist of pied flycatchers and was found in low levels in the Swedish collared flycatcher population in our study (3.4%). It is interesting to note that the lineage is abundant in a population of pied flycatchers in the Central European contact zone in Poland (Dubiec, Podmokła, Harnist, & Mazgajski, ) and is absent in the Polish collared flycatchers in our study. However, it is possible that we have failed to detect this lineage in our relatively small sample size ( n = 67) of collared flycatchers from Poland.…”
Section: Discussionmentioning
confidence: 59%
“…hPHSIB1 appears to have a broader host range; also being present in 15 other passerine species. It is important to note that two of our populations of collared flycatchers (Czechia and Poland) lie in the historical contact zone between pied and collared flycatchers and while these populations are not directly sympatric with pied flycatchers, it is possible that they can be found in nearby woodlands (Dubiec et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although some flycatchers were infected already before their arrival to their breeding grounds [71][72][73], this study showed that Haemoproteus prevalence, Haemoproteus para-sitemia, Plasmodium prevalence, and Plasmodium parasitemia significantly increased during the breeding season. This shows that Haemoproteus and Plasmodium parasites mostly infected the breeding Pied Flycatchers during the current reproductive season.…”
Section: Discussionmentioning
confidence: 65%